Darkness unbound eaudiobook Dark angels series, book 1. - Arthur, Keri (Dark Angels, 2012)
New York Times best-selling author Keri Arthur received the coveted Romantic Times Career Achievement Award for her urban fantasy tales. In Darkness Unbound, Risa Jones' werewolf-and-aedh lineage allows her to see reapers-supernatural beings that escort the souls of the dead to the afterlife. But when Risa discovers that a practitioner of blood magic is preventing souls from moving on, she knows she must set things right before all hell breaks loose.